A TIME SERIES ANALYSIS OF STUDENTS’ ENROLMENT IN PAINTING IN LAUTECH ART SCHOOL, OGBOMOSO, NIGERIA - ABOKEDE, Olugbenga Oladeji (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A superior evaluation of students’ enrolment growth in painting in Lautech Art School needs a methodological approach that most research effort lack. Hence, this study generated Mathematical model to assess the trend, direction and students’ enrolment in painting with the effluxion of year. It also examined the influence of year factor in enrolment and correlation between enrolment in painting and other specialisation areas. Secondary data were sourced from students’ enrolment record in the office of the head of the department from 2003/2004 to 2023/2024 sessions. The analytical techniques employed to assess temporal variation in enrolment were exponential smoothing technique with a smoothing constant of 0.3 and the least square trend analytical technique was used for analysis. Regression and correlation coefficients represented by “b” and “r” respectively were used to examine the changing rate of the students’ enrolment in the period of years under investigation. The least square model generated is given with the equation y= 5.147 + 0.224 x, which implies that a unit increase in year, would bring about 0.224 unit increase in the case of students enrolment. Further analysis showed that enrolment exhibited a rising trend with the effluxion of year. The weak positive values (b = +0.224; r = +0.333) associated with enrolment status confirmed the positive lapse rate and direct relationships. The coefficient of determination (r2) in this case is 0.111 which implies that 11.11% of variations in the level of enrolment were influenced by (year factor) changes in year and 88.89% were explained by other factors. There was positive correlation (r= 0.353) between students’ enrolment in painting and enrolment in other specialisation areas in LAUTECH Art School. The study concluded that the growing rate of aggregated enrolment in other areas of specialisation is a bit faster than enrolment in painting.